Computer Vision Systems 10th International Conference, ICVS 2015, Copenhagen, Denmark, July 6-9, 2015, Proceedings - Nalpantidis, Lazaros; Krüger, Volker; Eklundh, Jan-Olof; Gasteratos, Antonios (Theoretical Computer Science and General Issues, 2015)
This book constitutes the refereed proceedings of the 10th International Conference on Computer Vision Systems, ICVS 2015, held in Copenhagen, Denmark, in July 2015. The 48 papers presented were carefully reviewed and selected from 92 submissions. The paper are organized in topical sections on biological and cognitive vision; hardware-implemented and real-time vision systems; high-level vision; learning and adaptation; robot vision; and vision systems applications.